The Application of Restorative Justice Principles in Handling Corruption Offenses: State Loss Recovery as an Alternative Sentencing Model in Indonesia - Adhiwisata Tappangan; Supardi Supardi; Beniharmoni Harefa (International Journal of Social Sciences and Humanities, 2026)
Corruption constitutes an extraordinary crime because it causes state financial losses, obstructs national development, and harms public welfare. The handling of corruption offenses in Indonesia still relies heavily on a retributive model that prioritizes imprisonment. This model has not fully optimized state loss recovery. This study analyzes the current handling of corruption offenses and state loss recovery in Indonesia. It also examines the possible use of restorative justice as a limited and complementary sentencing approach. This study uses normative legal research with statutory, conceptual, and comparative approaches. Primary, secondary, and tertiary legal materials are analyzed qualitatively. The findings show that asset recovery in corruption cases remains weak because law enforcement still focuses on imprisonment as the main indicator of success. Restorative justice can support a more effective model by placing state loss recovery as a central objective without eliminating criminal liability. This study proposes the reformulation of Article 4 of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. The proposed formulation requires compensation of up to four times the amount of state loss caused by the offender. This concept can strengthen state financial recovery, increase deterrence, and balance legal certainty, justice, and legal utility.